2016
DOI: 10.15625/1811-4989/14/1/9305
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of fungal endophytes isolated from agarwood tree Aquilaria crassna Pierre ex Lecomte

Abstract: SUMMARYIn recent years, a considerable number of studies on the role of microbes in agarwood production have been carried out in plants of the species Aquilaria. Based on the fact that there is a relationship between the microorganisms residing inside the plant and the agarwood formation, we isolated and characterized endophytic fungi associated with A. crassna samples collected from Southern Vietnam. Morphological identification and DNA barcoding analysis of the fungal endophytic isolates indicated that they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Several endophytic fungi are known as potentially bioactive metabolite producers in Aquilaria trees, and this is used in agarwood-producing trees [54][55][56]. In this study, two endophytic fungi belonging to Nemania were isolated from the dark resinous wood of Aquilaria sinensis, collected from Xishuangbanna, and this is the first report of Nemania from the host genus Aquilaria.…”
Section: Discussionmentioning
confidence: 96%
“…Several endophytic fungi are known as potentially bioactive metabolite producers in Aquilaria trees, and this is used in agarwood-producing trees [54][55][56]. In this study, two endophytic fungi belonging to Nemania were isolated from the dark resinous wood of Aquilaria sinensis, collected from Xishuangbanna, and this is the first report of Nemania from the host genus Aquilaria.…”
Section: Discussionmentioning
confidence: 96%
“…Pembentukan aroma resin gaharu dan perubahan warna kayu gaharu pada proses infeksi buatan menggunakan inokulum dipengaruhi oleh faktor biotik dan abiotik. Faktor biotik terutama cendawan sebagai agen bio-induksi yang menentukan pembentukan resin gaharu harus bersifat endofitik-patogenik-epifitik (Chi et al 2016;Chippa et al 2017).…”
Section: Pengamatan Hasil Induksi Pohon Gaharuunclassified
“…Endophytic microorganisms, mostly fungi in general, are localized internally in their host plants and become an important issue in the past few decades (Faeth, 2002;Staniek et al, 2008) has been previously reports (Nimnoi et al, 2010;Shoeb et al, 2010;Chi et al, 2016).…”
Section: Endophytic Fungi Isolationmentioning
confidence: 99%
“…In this study, 50 endophytic fungal isolates were evaluated for antioxidant activity. The results revealed that among 50 isolates, six had ability to reduce the absorbance of DDPH free radical with the range was 36% -82% ( (Gong and Guo, 2009;Nimnoi et al, 2010;Shoeb et al, 2010;Cui et al, 2011;Chi et al, 2016) (Tanapichatsakul et al, 2018).…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation